Java TCP Server Load Balancer: Analysis And Comparison Of Its Load Balancing Algorithms - Abu Yan, Mohd Khir (2008)
A TCP server load balancer (SLB) programmed in Java is proposed as an affordable alternative to commercial or open source server load balancer for small companies by having all basic server load balancer features in order to maximize the usage of small companies financial, human and hardware resources.